Hubungan Perilaku Konsumtif dan Minat Mahasiswa Menggunakan Jasa Pinjaman Online - Mardikaningsih, Rahayu; Sinambela, Ella Anastasya; Darmawan, Didit; Nurmalasari, Dita (Universitas Nusantara PGRI Kediri, 2020)
In the current digital era, the presence of financial technology (fintech) has changed people's lives, including students. The existence of fintech that has been regulated in such a way allows students to easily access it. The perceived convenience is actually the cause of the emergence of consumptive behavior. Therefore, this study was conducted with the aim of finding out whether there is a relationship between consumptive behavior and student interest in using online loan services. The researcher targets that there will be 100 students selected to be respondents. The results of the study provide evidence that there is indeed a relationship between consumptive behavior and student interest in using online loan services.